PELATIHAN DESAIN GRAFIS PADA SMKS NURUL HUDA PRINGSEWU - Debby Alita; Yuri Rahmanto; Ade Dwi Putra; Suaidah Suaidah; Permata Permata (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2022)
Graphic design developers are very important for the world of work because graphic design is one of the points in the marketing process. One of the materials in graphic design is making posters. Posters have the main purpose of attracting attention, informing, convincing and provoking. If people feel called, posters can influence their decisions through text and images. Optimally designed posters attract the audience's curiosity, as well as unconsciously its emotional side. SMKS Nurul Huda has 3 majors, one of which is animation major, the service team intends to provide insight and knowledge to SMKS Nurul Huda students to be able to make posters so that when they have graduated from school students have been equipped with the knowledge of making posters to market products where where they work. Based on the results of the training, students were able to make 1 very interesting advertising poster.